Sevoflurane Alleviates Reperfusion Arrhythmia by Ameliorating TDR and MAPD90 in Isolated Rat Hearts after Ischemia-Reperfusion - Guilong Wang; Dongjun Dai; Hong Gao; Yanqiu Liu; Zijun Wang; Huayu Li; Xiaokui Fu (Anesthesiology Research and Practice)
Objective. To investigate the effect of sevoflurane on the monophasic action potentials (MAPs) in isolated rat hearts after ischemia-reperfusion. Methods. Twenty-four healthy SD male rats, weighing 280–320 g, were randomly divided into three groups after successful preparation of a Langendorff isolated heart perfusion model with a stabilization period perfusion of 15 min with Krebs–Henseleit (K–H) fluid (n = 8): the control group (group A, continuously perfused with K–H fluid for 105 min), the ischemia-reperfusion group (group B, continuously perfused with K–H fluid for 15 min, and then exposed to 60 min of global ischemia induced by Thomas solution followed by 30 min of reperfusion), and the sevoflurane group (group C, K–H fluid contained 1.0 MAC sevoflurane, and other procedures were same as in group B). Heart rate (HR) and MAPs including time course (MAPD50 or MAPD90) of the epicardium (Epi) and endocardium (Endo) were recorded at the time of balance perfusion for 15 min (T0), continuous perfusion for 15 min (T1), reperfusion for 15 min/continuous perfusion for 105 min (T2), and reperfusion for 30 min/continuous perfusion for 120 min (T3), and the transmural dispersion of repolarization (TDR) was calculated. The incidence of arrhythmia, time for restoration of spontaneous heart beat, and duration of arrhythmia were recorded during the period of reperfusion. Results. HR in group B and group C was lower at T2 and T3 than that in group A, while that in group B was significantly lower than that in group A at T2 and T3, and HR in group C was higher than that in group B at T2 and T3 (P<0.05). There was no difference of TDR in each group at T0 and T1 (P>0.05), while TDR in group B was increased at T2 and T3 compared with that in group C and group A (P<0.05). TDR in group C was decreased compared with that in group B at T2 and T3 (P<0.05), while there was no such difference between group C and group A (P>0.05). The time for restoration of spontaneous heart beat and duration of arrhythmia in group C were shorter than those in group B (P<0.05), while cardiac arrhythmia scores in group B were higher than those in group C (P<0.05). There was no difference of MAPD50 in each group (P>0.05). The MAPD90 in group B was much longer than that in other groups at T2 and T3 (P<0.05), while there was no such difference between group C and group A (P>0.05). The prolonged MAPD90 at T2 and T3 in group B strikingly differed from that at T0 and T1 (P<0.05). Nevertheless, there was no such difference in other groups at different time points (P>0.05). Conclusion. Sevoflurane alleviates reperfusion arrhythmia induced by myocardial ischemia-reperfusion through the shortening of MPAD90 in isolated rat hearts.